THE PERFORMANCE OF PRINCIPAL SCHOOL OF STATE HIGH SCHOOL 1 KLATEN ON THE BASED MANAGEMENT SCHOOL IMPLEMENTATION - Wartomo, Wartomo; Siswati, Kus Anjar (HIBRUL ULAMA, 2024)
This research was aimed to describe the performance of the principal school on the school-based management implementation included teacher empowerment, infrastructure management, and fund education management. The subjects were the principal and some teachers of State Elementary School 1 Klaten. This study was using ethnographic research approach. Methods of data collection was using observation, interviews and documentation. Data analysis used was triangulation. The results showed that the empowerment of teachers included holding regular and integrated training for teacher performance, conduct supervision of learning, creating a conducive climate for wrking, enhance the ability of teachers through courses, workshops, education and training, seminars, and classroom action research. The infrastrcture facilities management were distribution responsibility and authority to subordinates such as inventory learning aids, laboratory equipment, tables and chairs. The education budget managements included formation of treasurer team, for example, the school committee treasurer, BOS treasurer and rehabilitation funds treasurer, and so on who assigned appropriate authority and responsibilities to facilitate the supervision and monitoring of the optimalbudget utility. It is easier for the principal to monitor and carry out performance in the implementation of SBM.